A Comparison of Students' Critical Thinking Skills Based on Assessment Techniques in Natural and Social Sciences (IPAS) - Nurul Mukhlisa; Abd Halik; Fuji Ayu Astuty (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Critical thinking is a fundamental competency in Natural and Social Sciences (IPAS) learning; however, school-based assessment practices remain dominated by conventional techniques that primarily measure learning outcomes and provide limited insight into students’ thinking processes. This study aimed to compare the critical thinking skills of students assessed through authentic and conventional assessment techniques and to determine whether the two approaches produced significantly different outcomes. A quantitative quasi-experimental approach with a nonequivalent control group design was employed. The sample comprised 68 students, including 35 students in the experimental group and 33 students in the control group. Data were collected using an essay-based critical thinking test developed according to the FRISCO indicators: Focus, Reason, Inference, Situation, Clarity, and Overview. The data were analyzed using descriptive statistics, normality and homogeneity tests, N-Gain analysis, and an independent-samples t test. The findings showed that the experimental group achieved a higher mean posttest score than the control group (73.94 vs. 63.00). The data met the assumptions of normality (p > .05) and homogeneity (p = .236), while the independent-samples t test revealed a statistically significant difference between the two groups, t = 4.430, p < .001. The N-Gain analysis also indicated greater improvement among students assessed through authentic assessment than among those assessed through conventional assessment. These findings demonstrate that authentic assessment is more effective in supporting the development of students’ critical thinking skills in IPAS learning. This study contributes practical evidence that assessment practices incorporating process-oriented and performance-based tasks can provide a more comprehensive measure of students’ reasoning and strengthen the integration of critical thinking into elementary science and social science instruction.